Rethinking Electrification in Sub-Saharan Africa : Why we Should Stop Counting and Start Thinking Big - World Bank (World Bank, Washington, DC, 2019)
If African nations want to see their economies transform, the issue of electricity must be tackled head-on. Expansion needs investment too, and for that, utilities must recover their costs. Yet all over the region utilities are running at a loss. This report takes a broader look at the issue to show that the problem in Africa is not power but poverty. It shows that affordability, reliability, and coordination are the missing links to making utilities financially viable and expanding their consumer base. The report emphasizes that access to electricity cannot be a stand-alone goal. Policymakers must rethink their approach to electrification by placing the productive use of electrification at center stage. Given the resource constraints, governments need to coordinate investments in other aspects of their infrastructure at the same time as they invest in electricity. Policies and programs need to focus on improving access to markets through better roads and expanding credit for new businesses. In this way, electricity can energize agriculture in rural areas and industry in urban areas. This report shows that, to generate income, create jobs, and alleviate poverty in Africa, electricity has to be part of a package.